KEKUASAAN DAN MORALITAS *SEBUAH PENGANTAR KEARAH PEMAHAMAN ORGANISASI - Rumijati, Aniek (Jurnal Bestari, 2001)
The power and morality is to be a pairs in the human civilization, and illustrate the culture,, social system of the society. Power and authority needs legitimation support to applicate due to the its basic orientation thet power / and authority talking about controls a man to the others. The power is the way of thinking and the way of doing. However, the power or authority needs ecological sound, specially in orientation of morality. In relation to motivication and morality in the social ecosystem, there is the looser and the winner, at once. Then , it could be arise the prey and predator of power of authority. The rule of conduct is one ofinterested motive to assess in discussion about power of authority.